The relationship between news media consumption and civic responsibility among university students - Subramaniam, Tilagavati; Tamam, Ezhar; Bolong, Jusang; Waheed, Moniza (AkiNik Publications, 2021)
This study examined whether the use of various types of media for news consumption would influences young people civic responsibility through a survey of university students in Malaysia. This study expands the literature on the issue of civic responsibility by looking at the effects using of different media types such as: television, newspapers, radio, and the Internet. Despite a significant worldwide decline in youth civic responsibility, few researchers investigated the inter-relationship between these two variables in a Malaysian context. Civic responsibility means active participation in the public life of a community in an informed, committed and constructive manner, with a focus of common goal. Civic responsibility is an attitudinal measure of obligation towards serving or creating change in one’s community (Mccrillis, 2013). Data are obtained through a survey questionnaire to total of 606 respondents from three public research universities in Malaysia. Respondents’ ages ranged from 21 to 31 years. This study employs quantitative method using correlation to determine relationship between these two variables. The result shows that a strong, positive correlation between news consumption and civic responsibility, which is statistically significant among final year undergraduate students. The internet and various media associated with it have greatly increased the capacity of university students in Malaysia to consume the news and participate in a greater variety of civic activities. Higher education transforms communities by providing students with information and competence from which they can plays significant roles within societies. This can lead to a healthier community, more skilful graduates both in their disciplines and soft skills, and in the long run, a more successful nation.